A Holistic, Reconciliatory, And Mediative Foundation In Contemporary Exegesis And The Implementation Of Modern Human Resource Management - Syuhada, Wira; Putra, Maha; Ilman, Zidni (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This study examines the integration of Qur’anic values into modern Human Resource Management (HRM) through a holistic, reconciliatory, and mediative paradigm. Using thematic exegesis (tafsīr mawḍū‘ī) and critical-hermeneutical analysis, the research reconstructs the Qur’anic worldview to address contemporary organizational challenges marked by spiritual emptiness, value fragmentation, and ethical crises. Primary sources from the Qur’an, hadith, and classical to modern tafsir are combined with recent HRM literature and best-practice organizational reports. The findings demonstrate that maqāṣid-based recruitment, spiritual–professional training, and justice-oriented compensation significantly enhance organizational outcomes, as evidenced by reduced turnover (35% at Bank Syariah Mandiri), strengthened leadership capacity (Telkomsel), high conflict-resolution success (89% at Pertamina), and improved innovation (67% at Microsoft Indonesia). The study also highlights the relevance of Qur’anic principles in addressing global issues such as mass layoffs, gender inequality, and ecological degradation through practical implementations by Amazon, Gojek, Unilever, and Pertamina. Overall, this research offers an integrated Islamic HRM model rooted in Qur’anic ethics, demonstrating its capacity to produce a just, sustainable, and human-centered management framework aligned with contemporary organizational demands.